Correlation Analysis between Parenting Patterns and Ability to Keep Independent Dental and Oral Cleanliness for Mentally Retarded Children - Sindi Anggela sindi; Isnanto Isnanto; Bambang Hadi Sugito (International Journal of Advanced Health Science and Technology, 2022)
Children with mental retardation often experience problems related to dental and oral health, including periodontal disease, caries, and poor OHI-S this is due to an unclean oral cavity. In addition, parenting in everyday life can also affect a child's ability to maintain and care for his oral cavity. This study aims to determine the correlation between parenting pattern and ability to keep independent dental and oral hygiene cleanliness for mentally retardarded children at SLB-B Negeri Pembina Palembang. This type of research is an analytic observational study with a cross-sectional design. Data collection methods are questionnaires and observations. The research respondents were the parents of 100 mild mental retardation children by simple random sampling. Data analysis using Chi-Square test. The results showed that 55% of children's ability to maintain dental and oral hygiene was still lacking, and categorized in the poor category. 62.2% of parents with democratic parenting have children in the capable category. The results of the Chi-Square test obtained a value of P = 0.041 so that P < = 0.05. Thus, there is a significant relationship between parenting pattern and ability to keep independent dental and oral hygiene cleanliness for mentally retardarded children at SLB-B Negeri Pembina Palembang. The benefit of this research is to provide knowledge so that parents can apply good parenting and find ways to improve their ability to maintain oral hygiene independently, especially for mentally retarded children.